The effect of thiol structure on allyl sulfide photodegradable hydrogels and their application as a degradable scaffold for organoid passaging - Yavitt, F. Max (Adv Mater, 2020)
Intestinal organoids have proven to be useful in vitro models for many basic and translational studies aimed at understanding and treating disease. However, their routine culture relies on animal derived matrices that limit their utility for clinical applications. In fact, there are few fully defined, synthetic hydrogel systems that allow for the development and expansion of intestinal organoids. Here, we present an allyl sulfide photodegradable hydrogel, achieving rapid degradation through radical addition-fragmentation chain transfer reactions, to support the routine passaging of intestinal organoids. We use shear rheology to first characterize the effect of soluble thiol and allyl sulfide crosslink structures on degradation kinetics. Irradiation with 365nm light (5 mW cm(−2)) in the presence of a soluble thiol (glutathione at 15 mM), and a photoinitiator (lithium phenyl-2,4,6-trimethylbenzoylphosphinate at 1mM), led to complete hydrogel degradation in less than 15 seconds. Allyl sulfide hydrogels were used to support the formation of epithelial colonies from single intestinal stem cells, and rapid photodegradation was used to achieve repetitive passaging of stem cell colonies without loss in morphology or organoid formation potential. This platform could be used to support long term culture of intestinal organoids, potentially replacing the need for animal derived matrices, while also allowing systematic variations to the hydrogel properties tailored for the organoid of interest.